Metode Naratif Eksperiensial Berbantuan Media Visual Sebagai Strategi Pengembangan Kemampuan Bernalar Kritis Kelas VIII Fase-D SMPN 2 Delang, Lamandau - Angelius Noveriwanto; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
The critical thinking ability of students in Catholic Religious Education at SMP Negeri 2 Delang class VIII is still relatively low. Students also struggle to connect the narrative of the Holy Bible with real-life experiences. This study aims to improve students' critical thinking skills and academic performance through the application of the Experiential Narrative Method supported by visual media. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 5 class VIII students (2 male and 3 female) during the odd semester from September to November 2024. The material in cycle I focused on the Passion and Death of Jesus as a symbol of human rejection, while in cycle II, the Resurrection of Jesus was used as a symbol of the Father’s acceptance. Data were collected through observations to assess critical thinking skills, and cognitive aspects were measured through written tests. The results showed significant improvement in the students’ critical thinking process. The average cognitive test scores increased from the initial test (63.60), to 75.60 in cycle I, and 82.8 in cycle II, reaching the target of 100% mastery. Student engagement also increased, moving from a less active category to very active. This study concludes that the experiential narrative method, enriched with visual media, is highly effective in enhancing critical thinking skills, cognitive learning outcomes, and overall student engagement.